In vitro digestibility and fermentability of fructo-oligosaccharides produced by Aspergillus ibericus - Nobre, C. (2018)
The bifidogenic potential of fructo-oligosaccharides (FOS) produced by a newly isolated strain – Aspergillus ibericus was studied. Their activity was compared to FOS produced by Aureobasidium pullulans and to a nonmicrobial commercial FOS sample (Raftilose® P95). FOS fermentability by a number of probiotic bacteria and their hydrolytic resistance to the simulated harsh conditions of the digestive system was evaluated. Aspergillus ibericus FOS sample effectively promoted probiotic bacteria growth. Overall, microbial-derived FOS promoted greater cellular growth compared to the commercial sample. FOS fermentation was both substrate and strain specific. The FOS structural differences identified may explain their distinct assimilation by the probiotics. [Fru (2→6)Glc] (possibly blastose) and a reducing trisaccharide (possibly [Fru(β2→6)Glc(α1↔β2)Fru], neokestose) were only found in microbial-derived FOS samples, while Raftilose® P95 was richer in inulobiose/inulotriose. 1- Kestose and nystose were only slightly hydrolyzed in the presence of gastric and intestinal fluid. FOS synthesized by Aspergillus exhibited great potential as food ingredients with likely prebiotic features.